Neem and Small Farmers - Constraints at Grass Root Level - Hegde, Narayan G. (Indian Forester, 1995)
Neem is a versatile tree of the tropics with immense potential to protect the environment while developing sustainable agriculture. Apart from its tolerance to drought and saline conditions, neem can contribute to the income of the rural people through production of seeds. However, neem cultivation is not popular because of lack of awareness about its benefits and economic advantages. To improve the productivity of neem and to popularise the cultivation, particularly among small farmers, it is necessary to formulate a strategy which will include the standardisation of propagation techniques, selection of superior germplasm, development of low cost silvicultural techniques, orientation of farmers to proper collection and processing of seeds and establishment of a strong extension network to highlight the benefits of neem in improving the economy and protecting the environment.